PRELIMINARY NUMERICAL ANALYSIS FOR THE ROLE OF SPEED ONTO LASER TECHNOLOGICAL PROCESSES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Studying the impact of speed on a number of laser processes such as marking, engraving, cutting, welding and others is crucial for the optimization of these technological processes. The processing speed, along with the frequency of laser pulses and their duration, also determines the time of action in the processing area and hence the absorbed quantity of electromagnetic energy. Based on numerical experiments with specialized software TEMPERATURFELD3D, the report analyzes the temperature variation in the processing area as a function of speed. The researches were analyzed for processing with two types of lasers emitting in the visible and infrared areas of the electromagnetic spectrum and two types of steels (tool and structural). From the course of the obtained temperature fields the dependence of temperature on the speed at two power densities was obtained. The obtained results help to make a preliminary assessment the speed work intervals for the processes as laser marking, laser engraving, laser cutting, laser welding and others. In this way, it is assisted in building an optimal concept for the passing of a particular technological process in function of the laser source, the material and the type of the technological operation.